2013
DOI: 10.1007/s11434-013-5686-5
|View full text |Cite
|
Sign up to set email alerts
|

Home risk factors for childhood pneumonia in Nanjing, China

Abstract: Pneumonia is a major cause of childhood morbidity in China. Many studies of rural areas have found an association between pneumonia and air pollution from burning of bio-mass. The present study is of children living in urban, modern homes without burning of bio-mass. In order to investigate potential home risk factors associated with children's pneumonia, China Child Home Health (CCHH) questionnaires were randomly distributed to parents of 6461 children in 23 kindergartens in all 11 districts of Nanjing, cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 21 publications
(25 reference statements)
4
14
0
Order By: Relevance
“…The children in this study are primarily living in new and modern apartments with lower air exchange rates than old apartments (see articles from Nanjing [65], and Urumqi [59] for further discussion).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The children in this study are primarily living in new and modern apartments with lower air exchange rates than old apartments (see articles from Nanjing [65], and Urumqi [59] for further discussion).…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was tested in a pilot study of 100 children in Chongqing in April 2010, and thereafter adjusted to improve readability. For details about questionnaire design, see articles for specific CCHH cities [58][59][60][61][62][63][64][65][66][67][68]. …”
Section: Questionnaire Design and Pilot Studymentioning
confidence: 99%
“…[18], Wang, T. [19], Zhang, M. [20], Zheng, X. [21], Wang, H. [22] et al conducted cross-sectional survey in Taiyuan, Urumqi, Wuhan, Nanjing, Chongqing and other cities in China during 2011e2012. All these results demonstrated that among these environmental factors, the indoor dampness increase the incidence of childhood asthma, rhinitis and other respiratory disease.…”
Section: Introductionmentioning
confidence: 99%
“…1 A CCHH questionnaire survey was used to investigate health outcomes and home environmental exposure of children of less than 8 years old in Nanjing. 1,12 The health part of the questionnaire was consistent with International Study of Asthma and Allergies in Childhood, and the questionnaire in relation to the environmental factors was similar to that of the dampness in building and health study conducted in Sweden 13 but with appropriate modifications due to different Chinese building characteristics. A total of 83 questions were included in the questionnaire covering six sections, i.e.…”
Section: Questionnairementioning
confidence: 74%